Electrochemically Modified Carbon and Chromium Surfaces for AFM Imaging of Double‐Strand DNA Interaction with Transposase Protein. Issue 2 (4th January 2013) - Esnault, Charles; Chénais, Benoît; Casse, Nathalie; Delorme, Nicolas; Louarn, Guy; Pilard, Jean‐François
Abstract Carbon and chromium surfaces were modified by electrochemical reduction of a diazonium salt formed in situ from the sulfanilic acid. The organic layer formed was activated by phosphorus pentachloride (PCl5) to form a benzene sulfonil chloride (ArSO2Cl). An electrochemical study of the blocking effect and the activity of this surface was carried out on a carbon electrode. The chromium surface study was completed by X‐ray photoelectron spectroscopy and atomic force microscopy to characterize the formation of a compact monolayer (0.8 nm height and roughness 0.2–0.3 nm). The compactness and the activity of this organic monolayer allowed us to affix a length dsDNA with the aim of analyzing the formation of a complex between dsDNA and a protein. The interaction of a transposase protein with its target dsDNA was investigated. The direct imaging of the nucleoproteic complex considered herein gives new insights in the comprehension of transposase–DNA interaction in agreement with biochemical data.